As Mulheres da Ciência: uma análise dos livros didáticos de Biologia aprovados no PNLD 2012, 2015 e 2018 - Ferreira, Alessandra Pavolin Pissolati (2010)
The study, carried out within the scope of the Education in Science and Mathematics Research Line of the Post-Graduate Education Program of the Federal University of Uberlândia, responds to the following research question: What places do women of science hold in Biology textbooks approved by PNLD? From this question, our main goal was to investigate the (in)visibility of women in Science within Biology textbooks approved by three editions of the National Textbook Program (PNLD) - 2012, 2015 and 2018. Our specific goals were to identify the presence of women of Science in these artifacts, as well as to indicate the themes, contents and subjects associated with them; and also, to identify, in the editions of the books, the continuities and/or ruptures in the approach of women of Science. From a methodological perspective, it is a qualitative study that uses a descriptive process and cultural analysis, since it takes a set of 36 Biology textbooks approved by the National Textbook Program (PNLD) - 2012, 2015 and 2018, the corpus of the research, as cultural artifacts. They convey a set of senses and meanings that, in turn, produce and announce ways of being and living in society; they operate in the construction of the identities of school's individuals and define, in different ways, who are scientists and the places that women and men of Science hold. Thus, we take gender as a category of analysis and construction of knowledge, in order to apprehend the intertwining of gender and Science in these artifacts when saying about women of Science. To undertake these problematizations, we take the Cultural Science Studies and Feminist Studies as theoretical references to read and analyze our artifacts in search of the places that they position women of Science. In this movement, what was evidenced by the investigation is the fact that the place occupied by the women of Science within the analyzed biology textbooks is not fixed. Although they are predominantly positioned in the accessory texts of these artifacts, the way they are presented is varied. The location of women of Science is surrounded by a diversity of knowledge in the field of Sciences, also including other areas of knowledge, such as Social Sciences. In Biological Sciences, more women of Sciences are presented in contents about Genetics, than in contents related to Zoology and Botany. The presence of women of Science is crossed by processes of (in) visibility and erasure. Therefore, we understand that the analyzed biology textbooks present continuities in the approach of women of Science in accordance with the history of Science, marked by an androcentric bias. On the other hand, we also identified discontinuities and ruptures in these artifacts in the way of approaching women in Science, which shows their potential to subvert the dominant discourse that says scientists are men. We understand that these discontinuities and ruptures are resonances of the discussions and problematizations about the intertwining of gender, Science and Education, which are essentials in the search for a non-sexist scientific education. The textbooks, when operating with representations of Science and scientists, mobilize behaviors and practices that establish rules and ways to regulate life and bodies. To problematize such an operation made it possible to broaden the debate on the intertwining of gender and Science in Basic Education.